Development of ludic course for english for children from 5 to 10 years FANLYC, David, Chiriquí 2017 - Moreno B., Eda M.; De Gracia, Edward (David, Panamá : UDELAS, 2017)
This project is based on the teaching support of a ludic course aimed to children from 5 to 10 years. It will provide these children basic knowledge from numbers to colors. In addition, they will be able to hold a simple conversation , make questions and answer them as they visit places on tour, read signs of the place they visit and understand what they say.
GENERAL INDEX CHART INDEX GRAPH INDEX INTRODUCTION CHAPTER I: Referential framework of the project CHAPTER II: DESCRIPTION OF THE PROJECT: 2.1. Theoretical framework 2.1.1. Ludic method 2.1.2. Function of a ludic method 2.1.3. Basic theories that support use of ludic activities 2.1.3.1. Whole language approach 2.1.3.2. Neurolinguistic programming activities in the classroom 2.1.3.3. The lexical approach 2.1.3.3.1. Lexical approach activities in the classroom 2.1.3.4. Competency based language teaching 2.1.3.5. Contest based language approach 2.1.4. Teacher's role for ludic activities 2.1.5. Classification of games according to its mobility in education 2.1.6. Benefits of using educational games to teach english 2.2. Proposal intervention 2.3. Organizational structure of the project management 2.4. Operational spefification of the done activities and tasks 2.5. Project products 2.6. Project development chronogram 2.7. Budget CHAPTER III: RESULTS ANALYSIS Conclusion Recommendations References Annexes
Incluye General Index
Incluye Chart Index
Incluye Graph Index
Documento presentado para optar por el Título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
Keywords: ENGLISH -- PROYECTO DE LICENCIATURA -- TEACHING; ENGLISH -- PROYECTO DE LICENCIATURA -- METHODOLOGY; FACULTAD DE EDUCACIÓN ESPECIAL Y PEDAGOGÍA; ESCUELA DE PEDAGOGÍA; LICENCIATURA EN DOCENCIA EN INGLÉS; ENSEÑANZA DEL INGLÉS - NIÑOS; FANLYC - CHIRIQUÍ - PANAMÁ